“Por su culpa la mate...” Feminicidio de pareja en el Estado de México - Delgadillo Guzmán, Leonor Gpe (Archivos de criminología, seguridad privada y criminalística, 2021)
The objective of this qualitative investigation was to explore the significance of homicide against women, perpetrated by their heterosexual partners in sentenced persons of the State of Mexico. It was theoretically based on sociological phenomenology and the gender perspective. Six male homicidal partners were interviewed, the corresponding legal files were consulted. The categories of analysis were role and violence. The findings suggest as risk factors of homicidal action poverty, limited education, meager access to resources, and low-paid jobs with no or little social recognition. It shows the pattern of violent interaction between the couple, as well as the risk factors, vulnerability-sinisterness of gen